Encountering Chiefs in (a Search for) the State - Sade, Alexis Tucker (Anthropologica, 2020)
Since Pacific islands began achieving independence in the 1960s, the fate of traditional politics amid the adoption of Western governance systems and global economic integration has attracted anthropological attention. Four decades on, while some version of Western liberal democratic statehood is commonplace, customary institutions and ideologies remain salient in the fabric of many Pacific island societies. Rather than spelling their demise, introducing foreign political orders has, in places, brought about a revival and reimagining of traditions in reaction to the experiences of decolonisation and global politico-economic incorporation. In Solomon Islands, at independence, the constitution acknowledged the importance of customary practices and leadership in shaping the country’s path forward. However, there has been minimal formalisation within modern politics, prompting the question: What is the relationship between chiefs and the state in Solomon Islands? Chiefs, more often, are seen as guardians of custom, concerned with matters outside the realm of modern statehood or, in some cases, in opposition to it. This characterisation, however, hinges on particular conceptualisations of the state, thereby excluding other interpretations of modern political organisation including the roles that traditional political forms play in constituting relations referred to as the state.